Advancing Patient‐centered Outcomes in Emergency Diagnostic Imaging: A Research Agenda. (17th November 2015) - Kanzaria, Hemal K.; McCabe, Aileen M.; Meisel, Zachary M.; LeBlanc, Annie; Schaffer, Jason T.; Bellolio, M. Fernanda; Vaughan, William; Merck, Lisa H.; Applegate, Kimberly E.; Hollander, Judd E.; Grudzen, Corita R.; Mills, Angela M.; et al.
Abstract: Diagnostic imaging is integral to the evaluation of many emergency department (ED) patients. However, relatively little effort has been devoted to patient‐centered outcomes research (PCOR) in emergency diagnostic imaging. This article provides background on this topic and the conclusions of the 2015 Academic Emergency Medicine consensus conference PCOR work group regarding "Diagnostic Imaging in the Emergency Department: A Research Agenda to Optimize Utilization." The goal was to determine a prioritized research agenda to establish which outcomes related to emergency diagnostic imaging are most important to patients, caregivers, and other key stakeholders and which methods will most optimally engage patients in the decision to undergo imaging. Case vignettes are used to emphasize these concepts as they relate to a patient's decision to seek care at an ED and the care received there. The authors discuss applicable research methods and approaches such as shared decision‐making that could facilitate better integration of patient‐centered outcomes and patient‐reported outcomes into decisions regarding emergency diagnostic imaging. Finally, based on a modified Delphi process involving members of the PCOR work group, prioritized research questions are proposed to advance the science of patient‐centered outcomes in ED diagnostic imaging.